2002
DOI: 10.1034/j.1600-0412.2002.811008.x
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture in the management of pain in labor

Abstract: The results indicate that acupuncture reduces the experience of pain in labor. A secondary outcome of acupuncture was a shorter delivery time, which mainly, if not exclusively, can be explained by the reduced need for epidural analgesia. Acupuncture may be useful for parturients who wish a nonpharmacological analgesia without side-effects. For others it could be the analgesic method of choice, with pharmacological analgesics as supplements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 9 publications
3
52
2
3
Order By: Relevance
“…15 Participants and settings A total of 2038 participants were involved, ranging from 90 to 607 per study. Four studies recruited only nulliparous women; [16][17][18][19] five studies had both nulliparous and multiparous women; 15,[20][21][22][23] and parity was not mentioned in one study. 24 The majority of the studies included women at more than 37 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…15 Participants and settings A total of 2038 participants were involved, ranging from 90 to 607 per study. Four studies recruited only nulliparous women; [16][17][18][19] five studies had both nulliparous and multiparous women; 15,[20][21][22][23] and parity was not mentioned in one study. 24 The majority of the studies included women at more than 37 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…24 The majority of the studies included women at more than 37 weeks of gestation. All studies were conducted in hospital settings: five in Europe, 15,[20][21][22][23] three in China, [16][17][18] and two in Iran. 19,24 Potentially relevant articles reviewed and retrieved for more detailed evaluation (n = 92) …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acupuncture seems to help women manage labour pain and avoid pharmacological pain relief, though it is still unclear if acupuncture can reduce pain intensity [2,3]. Some studies have found that acupuncture leads to a reduction of pain during labour [4,5], whereas other studies have not [6][7][8][9]. Three studies, however, reported that acupuncture leads to a reduced use of pharmacological pain relief such as epidural analgesia and pethidin [6,7,10].…”
Section: Introductionmentioning
confidence: 91%